THE ROLE OF ACEH GOVERNMENT IN PROMOTING THE USE OF ACEHNESE AS A REGIONAL LANGUAGE - Rahil Helmi; Siswantia Sar (Faculty of Letters Universitas Balikpapan, 2024)
Bahasa Aceh is a local language which has a unique history and characteristics that set it apart from other local languages in Indonesia. However, the everyday use of Acehnese language is increasingly influenced by Indonesian and other foreign languages. Therefore, this research aims to investigate the role of the Aceh government in preserving and promoting Acehnese as a valuable regional language. This research employs a descriptive qualitative method by collecting data through surveys, interviews, document studies, and participatory observations with government officials, cultural experts, and the public who use Acehnese language in their daily lives. The data was analysed by summarizing the survey results, interviews, document studies, and observations. The research findings indicate that the Aceh government has played a positive role in preserving and promoting Acehnese language by establishing regulations and rules in the Aceh province, providing Acehnese language training to the community to enhance their understanding and proficiency in Acehnese, and developing Acehnese culture using Acehnese language in arts and cultural activities.